Umpan balik dan Evaluasi Terhadap kinerja Organisasi: A Literature Review - Mahyadi Mahyadi; Mochammad Isa Anshori (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Feedback is information provided to individuals about their performance and can help them understand the difference between desired performance and actual performance achieved. Individuals with high self-evaluation tend to assess job demands in a more positive manner and have a greater ability to face or overcome those demands. High self-evaluation can influence individuals' perceptions of work situations and have a positive impact on job satisfaction. This systematic review is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The databases used were Scopus, SAGE full-text articles, and the language of publication was English. The keywords used in the article search were "Self-Evaluation" and "Feedback". After identifying several articles, the authors analyzed and synthesized them according to the inclusion and exclusion criteria set for this study. The findings indicate that manager performance evaluations using the Balanced Scorecard (BSC) pay more attention to general actions than to unique actions, unless cognitive feedback is given to highlight the importance of using all actions. This underscores the importance of considering behavior as the ultimate outcome of the feedback provided. This research also aims to create a better work environment through the acceptance of constructive feedback and the appropriate use of feedback. High-quality feedback is an important factor in the context of learning and individual performance in the workplace. Overall, these studies provide a better understanding of the importance of feedback in the context of learning, performance, and individual development in the workplace. Dialogic feedback, self-evaluation, and consistent feedback systems can help create a better work environment and improve individual performance and job satisfaction.